Analisis Pestisida Karbaril dengan metode KLT- Densitometri dalam matriks kedelai dan validasi metodenya - Sugijanto; Prihatin; Noor Erma Sugijanto (The East Java Biological Society, 2010)
A simple and rapid densitometric method has been developed for determination of low levels of carbaryl in soy bean matrix samples. Sample carbaryl in the soybean matrix was extracted with acetonitril, chloroform and NaCl 0.2 % solution, and the resulting chloroform layer was separated, added sodium sulphate anhydrous to get free of water than evaporated. After dissolution in methanol, the solutions were spotted on silica gel GF254 plates which were then eluted with toluene: ethyl acetate = 3:1 (v/v). Quantitative evaluation was performed by measuring the absorbance reflectance of the analyte spots at λ 280 nm. This densitometric method is selective, precise, accurate and can be used for the determination carbaryl in soy bean matrix.